Effective hygromycin concentration for selection of Agrobacterium-mediated transgenic Arabidopsis thaliana - Ee, S.F.; Khairunnisa, M.B.; Zeti-Azura, M.H.; Noor Azmi, S.; Zamri, Z. (Penerbit Universiti Kebangsaan Malaysia, 2014)
The floral-dip transformation method for Arabidopsis thaliana has long been established. Following transformation, an important step is involving the selection for transgenic plants through antibiotics or herbicides. Hygromycin has been widely applied for transgenic plants selection. However, the concentrations used were varied between laboratories mostly in a range of 10 mg/L up to 200 mg/L. In the present study, the hygromycin sensitivity test was performed on wild-type seeds to obtain the most effective hygromycin concentration for selection of the transgenic. A standard curve on average mean of hypocotyls lengths against hygromycin concentrations was constructed. Based on hypocotyls length and leaf colour, the most effective concentration of hygromycin was determined in the range of 20 to 30 mg/L. For screening the transformed seeds, hygromycin concentration at 25 mg/L was used. Non-transgenic plants demonstrated a clear decrease in hypocotyls lengths and no root elongation, as compared to transgenic plants. The identified transgenic seedlings were further verified through polymerase chain reaction (PCR), giving fragment with an expected size of 365 bp.